EVALUATION OF RADIATION EXPOSURE OF SOME SELECTED URANIUM-ORE PITS WITHIN ZING, YORRO AND JALINGO LOCAL GOVERNMENT AREA OF TARABA STATE, NIGERIA - Rasheed, Lawal S.; Ibrahim, U.; Yusuf, Samson D.; Mundi, Abdullahi A.; Idris, Mustapha M. (FUDMA JOURNAL OF SCIENCES, 2025)
This study’s aim at assessing radiological exposure from abandoned uranium pits in Taraba State. The exposure level was made with the aid of a survey meter model GQ-GMC-500+ while the coordinates and elevation of each mine site were determined by a GPS. The mean values of background exposure levels (0.2691μSv/h) at the excavation point, (0.2493μSv/h) at 500m away from the mine pits, they are higher than the recommended safe limits of 0.13μSv/h (ICRP,2003). Absorbed dose rates (2.691E-04ηGyh-1) lower compare to 84ηGyh-1(UNSCEAR,2000). The mean annual effective dose equivalent (3.30E-04mSvy-1) is within recommended permissible limits of 1.00 mSvy-1 for general public exposure. Lifetime cancer risk value of 1.91E-02 is above the permissible benchmark value of 0.29x10-3 (UNSCEAR, 2000). Findings indicate exposure levels are above international safety thresholds, suggesting maximum current radiological risk, though periodic monitoring is recommended to safeguard public health. Generally, the study shows that Taraba mining spots are radiologically contaminated due to excavation and illegal mining operation. However, the contamination has no immediate radiological health risk on the inhabitants, but there is possibility of long-term health burden in the future, such as cancer, due to public exposure.